2018
DOI: 10.1177/1526924818800044
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality Among Renal Transplant Patients With Invasive Pulmonary Aspergillus Infection

Abstract: Introduction: Renal transplantation is the most effective and preferred definite treatment option in patients with end-stage renal disease. Due to long-term immunesuppressive treatment, renal transplant recipients become vulnerable to opportunistic infections, especially to fungal infections. Method: This was a single-center, retrospective observational study of 438 patients who underwent renal transplantation between 2010 and 2016. Results: Thirty-eight renal transplant recipients who had lower respiratory tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…However, immunosuppression increases the risk of opportunistic infections and induces the occurrence of secondary fungal infections with high mortality rates (40-60%). 1,3 Voriconazole is the first available second-generation triazole. Experts recommend voriconazole as primary therapy for invasive aspergillosis.…”
Section: How Might This Change Clinical Pharmacol-ogy or Translationamentioning
confidence: 99%
See 1 more Smart Citation
“…However, immunosuppression increases the risk of opportunistic infections and induces the occurrence of secondary fungal infections with high mortality rates (40-60%). 1,3 Voriconazole is the first available second-generation triazole. Experts recommend voriconazole as primary therapy for invasive aspergillosis.…”
Section: How Might This Change Clinical Pharmacol-ogy or Translationamentioning
confidence: 99%
“…Kidney transplantation, in conjunction with calcineurin inhibitors, is regarded as the best option for patients with end‐stage kidney disease. However, immunosuppression increases the risk of opportunistic infections and induces the occurrence of secondary fungal infections with high mortality rates (40–60%) 1,3 …”
mentioning
confidence: 99%
“…Fungi are responsible for around five percent of all infections in renal-transplanted patients and Aspergillus species is second only to Candida spp. in this cohort [ 7 ]. Invasive aspergillosis (IA) is a life-threatening opportunistic infection in immunocompromised patients including renal transplant recipients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high mortality rate has been observed in IA in renal transplants (40–60%) [ 1 , 12 ]. In some studies, it is as high as 67% to 92%; however, this may be due to the small number of cases of these studies [ 7 , 11 , 13 ]. For example, Gavalda et al observed the death of 7 out of 10 renal transplant recipients with IA in his retrospective case–control study, a 70% mortality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation